A Convex Optimization-Based Dynamic Model Identification Package for the da Vinci Research Kit - Wang, Yan; Gondokaryono, Radian; Munawar, Adnan; Fischer, Gregory Scott (IEEE robotics and automation letters, 2019)
The da Vinci Research Kit (dVRK) is a teleoperated surgical robotic system. For dynamic simulations and model-based control, the dynamic model of the dVRK is required. We present an open-source dynamic model identification package for the dVRK, capable of modeling the parallelograms, springs, counterweight, and tendon couplings, which are inherent to the dVRK. A convex optimization-based method is used to identify the dynamic parameters of the dVRK subject to physical consistency. Experimental results show the effectiveness of the modeling and the robustness of the package. Although this software package is originally developed for the dVRK, it is feasible to apply it on other similar robots.